2004
DOI: 10.1002/jcp.20225
|View full text |Cite
|
Sign up to set email alerts
|

Cell transformation byHerpesvirus saimiri

Abstract: Herpesvirus saimiri (Saimiriine herpesvirus-2), a g2-herpesvirus (rhadinovirus) of non-human primates, causes T-lymphoproliferative diseases in susceptible organisms and transforms human and non-human T lymphocytes to continuous growth in vitro in the absence of stimulation. T cells transformed by H. saimiri retain many characteristics of intact T lymphocytes, such as the sensitivity to interleukin-2 and the ability to recognize the corresponding antigens. As a result, H. saimiri is widely used in immunobiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 189 publications
(307 reference statements)
0
10
0
Order By: Relevance
“…Herpesvirus saimiri (HVS) is a T-lymphotropic virus that leads to leukemias and lymphomas in certain species of nonhuman primates (39,151). HVS encodes at least three gene products that modulate TcR function.…”
Section: Hivmentioning
confidence: 99%
“…Herpesvirus saimiri (HVS) is a T-lymphotropic virus that leads to leukemias and lymphomas in certain species of nonhuman primates (39,151). HVS encodes at least three gene products that modulate TcR function.…”
Section: Hivmentioning
confidence: 99%
“…Prior to stimulation, immunoblots revealed no detectable expression of TTP (Fig. 7A, lane 1), despite the fact that our HVS-transformed T cells appear to have an activated phenotype in many other respects (74). After stimulation of both wild-type and mutant HVS-transformed T cells of both cell sets, TTP expression was seen, with maximal induction occurring with 25 ng of PMA/ml and 625 ng of ionomycin/ml for 3 to 6 h (Fig.…”
Section: Vol 24 2004mentioning
confidence: 87%
“…Cultured T cells transformed by HVS show modified expression of cytokines and other ARE-containing genes, including IL-2, IL-3, gamma interferon, TNF-␣, TNF-␤, and a homolog of 39,74). Thus, it has been proposed that the ARE-containing HSURs compete with less abundant host mRNAs for host cell ARE-binding proteins in latently infected, transformed T cells (26,58).…”
mentioning
confidence: 99%
“…Lck kinase activity is increased by Tip [21,30,31], while several studies have indicated that Nef inhibits Lck kinase activity [11,18,19]. StpC, also a type II membrane protein interacts with the Ras GTPase, TRAF-2 and -6 and leads to increase NF-B activation (reviewed in Brinkmann and Schulz [8]; Tsygankov [45]). Since Tip and StpC interact with or influence host factors integral to HIV-1 replication we designed experiments to determine the role interactions between TMPs and host proteins have in the paradoxical effects of Tip and StpC on HIV-1 replication and reactivation.…”
Section: Introductionmentioning
confidence: 98%